DFT Conformational Study of Calix[6]arene: Hydrogen Bond - 김광호; 최종인 (Bulletin of the Korean Chemical Society, 2009)
We have performed DFT calculations to investigate the conformational characteristics and hydrogen bonds of the calix[6]arene (1) and p-tert-butylcalix[6]arene (2). The structures of various conformers of 1 were optimized by using the B3LYP/6-31G(d,p) and /6-31+G(d,p) methods followed by single point calculation of MPW1PW91/ 6-31G(d,p). The relative stability of the conformers of 1 is in the following order: cone (pinched: most stable) > partial-cone > cone (winged) ~ 1,2-alternate ~ 1,2,3-alternate > 1,4-alternate > 1,3-alternate > 1,3,5-alternate. The structures of different conformers of 2 were optimized by using the B3LYP/6-31G(d,p) method followed by single point calculation of MPW1PW91/6-31G(d,p). The relative stability of the conformers of 2 is in the following order: cone (pinched) > 1,2-alternate > cone (winged) > 1,4-alternate ~ partial-cone > 1,2,3-alternate > 1,3,5alternate > 1,3-alternate. One of the important factors affecting the relative stabilities of the various conformers of the 1 and 2 is the number and strength of the intramolecular hydrogen bonds. KCI Citation Count: 9